Annual World Bank Conference on Development Economics 2007, Global : Rethinking Infrastructure for Development (Annual World Bank Conference on Development Economics, 2007)
This edition of the Annual World Bank Conference on Development Economics presents selected papers from the ABCDE Meetings, held May 29-30, 2006, in Tokyo, Japan. This volume presents papers on Infrastructure for Growth - emerging issues; sustainable development and infrastructure - climate change, clean energy, and energy efficiency; rural infrastructure and agricultural development; and infrastructure and regional cooperation